A novel experimental technique and its application to study the effects of particle density and flow submergence on bed particle saltation. Issue 1 (2nd January 2017) - Amir, Mohammad; Nikora, Vladimir; Witz, Matthew
ABSTRACT: A novel technique has been developed to measure bed particle flight durations and amplitudes using the impact data from the records of instantaneous pressure acting on multiple bed particles. It has the potential to measure many more particle jumps compared to other methods, thus generating records long enough for well-converged statistics of the variables of interest. The proposed technique has been validated with independent measurements by a tracking method using a four camera particle image velocimetry system. The application of this technique in a laboratory study revealed that probability distributions and statistical moments of flight durations and heights are strongly dependent on flow submergence and particle density.